2021
DOI: 10.29333/iji.2021.1448a
|View full text |Cite
|
Sign up to set email alerts
|

The Employability Skills of Engineering Students': Assessment at the University

Abstract: Employability can be an alternative solution to increase individual chances of getting a job. The study aims to identify indicators that can measure students' employability skills and attributes. The research model, based on The Conference Board of Canada (Employability Skills 2000+), is divided into fundamental skills, personal management skills, and cooperative skills. The method used Confirmatory Factor Analysis (CFA) with primary data obtained from surveys of students through a questionnaire will be analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
2
13
0
3
Order By: Relevance
“…Researchers have identified that problem-solving skills are core to employability (Reid & Anderson, 2012;Yusoff et al, 2012;Asonitou, 2015;Ito & Kawazoe, 2015;Azmi et al, 2018;de Villiers Scheepers et al, 2018;Scott et al, 2019;de Campos et al, 2020;Fajaryati et al, 2020;Liew et al, 2020;Saleh & Lamsali, 2020;Zapalska et al, 2020;Idkhan et al, 2021). Similar to soft-skills, problem-solving skills are important across disciplines (e.g., engineering, marketing) and employer type (Wellman, 2010).…”
Section: Problem Solving Skillsmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have identified that problem-solving skills are core to employability (Reid & Anderson, 2012;Yusoff et al, 2012;Asonitou, 2015;Ito & Kawazoe, 2015;Azmi et al, 2018;de Villiers Scheepers et al, 2018;Scott et al, 2019;de Campos et al, 2020;Fajaryati et al, 2020;Liew et al, 2020;Saleh & Lamsali, 2020;Zapalska et al, 2020;Idkhan et al, 2021). Similar to soft-skills, problem-solving skills are important across disciplines (e.g., engineering, marketing) and employer type (Wellman, 2010).…”
Section: Problem Solving Skillsmentioning
confidence: 99%
“…In summary, the literature review indicates that researchers have identified problem solving skills as an important factor influencing EM (Reid & Anderson, 2012;Yusoff et al, 2012;Asonitou, 2015;Ito & Kawazoe, 2015;Azmi et al, 2018;de Villiers Scheepers et al, 2018;Scott et al, 2019;de Campos et al, 2020;Fajaryati et al, 2020;Liew et al, 2020;Saleh & Lamsali, 2020;Zapalska et al, 2020;Idkhan et al, 2021).…”
Section: Problem Solving Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lecturer must also understand limitations and needs, such as learning how to use data and how to organize and communicate their data. It involves critical thinking processes, personal and professional ethical awareness, evaluating information, conceptualizing information needs, collecting data, interacting with professionals [15], and using existing knowledge to solve decision-making and research. This information-based process is also essential in shaping learning character that needs to be supported by an information technology infrastructure.…”
Section: Introductionmentioning
confidence: 99%